Tissue morphology study: hematoxylin and eosin staining in healing process of full thickness wound animal model / Caroline Esther Paul - Paul, Caroline Esther (2014)
The healing process of full thickness wound is a complex process involving domination of different cells that each plays important roles in different phase of the healing process. The objective of this study was to elaborate a histological study of deep burn wound healing in rats. In this study, deep burn wounds were inflicted on the dorsal part of six anesthetized male rats. Histological sections from tissue specimen of the wounds harvested at day 0, 2, 7, 14, 21 and 28 post wounding were stained with hematoxylin and eosin. The histology of the wounds were correlated with stages in wound healing process. The inflammatory phase was observed at day 2 post wounding with infiltration of polymorphonuclear neutrophils in the wound bed. The proliferative phase was seen at days 7 and 14 post wounding with microscopic presence of blood capillaries and macrophages. Subsequently, the remodelling phase was observed at days 21 and 28 post wounding with domination of fibroblasts forming granulation tissue, filling the wound matrix. The wound healing phases were discussed based on the evaluation of the histological sections. This study serves as a preliminary study and the results of this study can be used as an experimental model for further research using pharmacological or physical intervention that can enhance the wound healing process.